Hva anekdotene rommer - Ellingsen, Gunnar (Tidsskrift for kulturforskning, 2016)
The Norwegian meteorologist Vilhelm Bjerknes (1862-1951), described by historians as the father of scientific meteorology, was himself an active writer of historical texts. The story about the "Bergen school of meteorology" as told by him and his assistants in various commemorative publications, still dominates historical understanding of meteorology. A number of anecdotes remain iconic in this story, and this article is an investigation of two of them. Through analysis of different layers of meaning in the anecdotes, the argument is that they reflect both smaller events and larger narratives and conceptions about science and the Norwegian people and nation. While the examined anecdotes represent personal glimpses on the past, they also offer wider views on nation and society, and the role of science.